Biomechanical analysis in equestrian vaulting - Vavácek, M.; Lednický, A.; Hajduová, K. (Acta Facultatis Educationis Physicae Universitatis Comenianae, 2018)
The authors focused on biomechanical analysis of the exercising shapes of the compulsory exercises in the equestrian vaulting. It is a sport sector in which similar observations have not been carried out. The use of 3D analysis brought the opportunity to observe the exercising shapes on a simulator and in real conditions on a horse. By the selected 3D approach they focused on three crucial phases of the swing back. This approach helped detect possible mistakes which the coach could not register from one position. The experimental set consisted of highly accomplished riders. The results confirmed that the higher the accomplishment level of a sportsman the fewer are the differences between the performances of an exercising shape. From the above mentioned we could assume that by including exercises on a barrel simulator into training units, we could influence the technique of performance of the individual exercising shapes on a horse in movement.